Histomorphological Study of Lymphoid Follicle of Vermiform Appendix - Rahman, MM; Begum, J; Khalil, M; Latif, SA; Nessa, A; Jahan, MK; Shafiquzzaman, M; Parvin, B; Akhanda, AH (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):134-40. The abstract of this article is available on the PubMed website